Research Methodology for Scientific Research - Prathapan K (New Delhi I.K. International Pvt. Ltd., 2023)
Perspectives of Scientific Research; Philosophy of Science; Getting Started with Research; Scientific Methodology; Data Collection and Analysis; Research in Practice; Scientific Writing; Preparation of Research Thesis; Ethics in Reseach; Publication Ethics.
Keywords: Research Methodology